2012
DOI: 10.1016/j.jams.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Isocratic HPLC Method for the Simultaneous Determination of Sinensetin, Eupatorin, and 3′-hydroxy-5,6,7,4′-tetramethoxyflavone in Orthosiphon stamineus Extracts

Abstract: Orthosiphon stamineus extracts contain three flavonoids (3'-hydroxy-5,6,7,4'-tetramethoxyflavone, sinensetin, and eupatorin) as bioactive substances. Previous reported high performance liquid chromatography- ultraviolet (HPLC-UV) methods for the determination of these flavonoids have several disadvantages, including unsatisfactory separation times and not being well validated according to International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 4 publications
1
29
0
1
Order By: Relevance
“…Several active chemical constituents that are prominently present in this plant are flavonoids (sinensetin and eupatorin) (Laavola et al, 2012; Yam et al, 2012) and a caffeic acid derivative (rosmarinic acid) (Olah et al, 2003; Pan et al, 2011). The chemical structures of sinensetin, eupatorin and rosmarinic acid are presented in supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several active chemical constituents that are prominently present in this plant are flavonoids (sinensetin and eupatorin) (Laavola et al, 2012; Yam et al, 2012) and a caffeic acid derivative (rosmarinic acid) (Olah et al, 2003; Pan et al, 2011). The chemical structures of sinensetin, eupatorin and rosmarinic acid are presented in supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interference with bacterial quorum sensing and biofilm production also appears to represent a promising intervention strategy (Wu et al, 2004; Balaban et al, 2007). At this juncture, we cannot rule out the possibility that UE-12 extract may also affect bacterial virulence as the plant extract contains numerous active constituents (Yam et al, 2012). It has been reported that plants possess compounds that can attenuate the virulence of a pathogen by inhibiting virulence factors including quorum sensing and biofilm formation (Adonizio et al, 2008; Rudrappa and Bais, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, O. stamineus leaf extract is widely used as an herbal remedy for kidney and urinary tract disorders. Previous studies revealed the anti-oxidant [51,52], anti-apoptotic [51], hepatoprotective [52] and gastroprotective [53] properties and also identified the major active fractions include eupatorin, sinensetin, 3′-hydroxy-5, 6, 7,4′-tetramethoxyflavone [54] and rosmarinic acid [55]. N. fruticans and O. stamineus extracts enabled the host to survive both antibiotic-sensitive and antibiotic-resistant S. aureus infection without interfering with bacterial viability, suggesting that these extracts possess compounds capable of targeting the host defense mechanism or attenuating bacterial virulence traits.…”
Section: Discussionmentioning
confidence: 99%
“…The total amounts of 3′hydroxy-5,6,7,4′-tetramethoxyflavone, sinensetin and eupatorin (purchase from Indofine Chemical Company, NJ, USA) in the 50% ethanol extract of O. stamineus were quantified using developed HPLC method (n = 3). The contents of these three compounds were expressed as percentages of the dried extract [18]. …”
Section: Methodsmentioning
confidence: 99%